2020
DOI: 10.1002/bse.2620
|View full text |Cite
|
Sign up to set email alerts
|

For green or not for green? The effect of cooperation goals and type on environmental performance

Abstract: Although many scholars have demonstrated that companies engaged in collaborations achieve better environmental performance than other companies, existing studies have not analyzed in depth whether this effect changes considering the characteristics of cooperation. Our paper aims to explore whether collaboration with other companies always has a positive effect on environmental performance or whether it depends on cooperation goals, collaboration type, or company size. Empirical analysis based on a sample of 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 94 publications
0
27
0
Order By: Relevance
“…Consistent with previous studies (e.g., Eklinder-Frick, Eriksson, & Hallén, 2014;Liao, 2018;Sahasranamam & Nandakumar, 2020) that highlight the role of social capital in the performance of SMEs, the current findings support the argument that social capital enables firms to gain access to physical resources such as technology and machinery essential in EM (Canevari-Luzardo, Berkhout, & Pelling, 2020;Hofmann, Theyel, & Wood, 2012 Fynes, 2020;Poon, Thai, & Naybor, 2012) by demonstrating that there is an empirically grounded and strong link between social capital and SME's pursuit for EM initiatives. The SME-focused measurement of social capital (concerning environmental sustainability) followed in this study fills the gap identified in previous studies, which used measures that were either distant from the context of SMEs in transition or developing economies (e.g., Liao, 2018) or too generic, qualitative and limited in scope (e.g., Calza, Parmentola, & Tutore, 2020;Canevari-Luzardo et al, 2018;Hoffmann et al, 2012) to capture the nuanced elements of social capital (or its related concepts such as…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Consistent with previous studies (e.g., Eklinder-Frick, Eriksson, & Hallén, 2014;Liao, 2018;Sahasranamam & Nandakumar, 2020) that highlight the role of social capital in the performance of SMEs, the current findings support the argument that social capital enables firms to gain access to physical resources such as technology and machinery essential in EM (Canevari-Luzardo, Berkhout, & Pelling, 2020;Hofmann, Theyel, & Wood, 2012 Fynes, 2020;Poon, Thai, & Naybor, 2012) by demonstrating that there is an empirically grounded and strong link between social capital and SME's pursuit for EM initiatives. The SME-focused measurement of social capital (concerning environmental sustainability) followed in this study fills the gap identified in previous studies, which used measures that were either distant from the context of SMEs in transition or developing economies (e.g., Liao, 2018) or too generic, qualitative and limited in scope (e.g., Calza, Parmentola, & Tutore, 2020;Canevari-Luzardo et al, 2018;Hoffmann et al, 2012) to capture the nuanced elements of social capital (or its related concepts such as…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…More than a century of rapid economic development has come at the price of global warming, water pollution, and deforestation, which are now critical global environmental problems (Jin et al, 2020). Despite debate over whether to be green or non‐green (e.g., Calza et al, 2021; Cuerva et al, 2014), businesses have recognized the need to respond appropriately to the perceived trade‐off between sustainable green view and economic performance. Though environmental sustainability is often considered a corporate goal, the relationship between environmental protection and industrial strategy has generally been viewed as a trade‐off between green performance and economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…A small and growing number of studies suggest that resource‐constrained SMEs can achieve environmental performance by leveraging strategic alliances with which they engage (Hofman et al, 2020; Lewis et al, 2015; Nakano & Hirao, 2011). Strategic alliances with customers, suppliers and/or competitors help an SME to access resources and knowledge that can allow the development of solutions for social and environmental issues (Adams et al, 2016; Calza et al, 2021; Palmieri et al, 2019; Stekelorum et al, 2020; Yen, 2018). However, strategic alliance is a risky activity and may fail due to differences in the expectations of partners (Chakravarty et al, 2020; Tukamuhabwa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%